PROGRAM MADRASAH ADIWIYATA DALAM MEMBENTUK KARAKTER PEDULI LINGKUNGAN BAGI SISWA MTS - Agus Wibowo; Hikmah Eva Trisnantari; Nanis Hairunisya (Jurnal Inovasi Penelitian, 2020)
The character of caring for the environment needs to be instilled in students from an early age. To foster the character of caring for the environment, starting with planning, implementing and evaluating programs in accordance with environmental management and preservation. The Adiwiyata Madrasah program was initiated and implemented by MTSN 3 Tulungagung starting in 2016.This study aims to determine the planning, implementation and evaluation of madrasah programs in shaping the character of caring for the environment for students in MTSN 3 Tulungagung. This research is a qualitative-descriptive research with a case study approach. The subjects in the study were the Head of MTSN 3 Tulungagung, Wakamad, Team Adiwiyata, GTK and students. Data collection techniques used are: observation, interviews, documentation, and data triangulation. Analysis of the data used is qualitative data analysis with data collection, data reduction, data presentation, and drawing conclusions. The results of the study showed that the Adiwiyata Madrasah Program in shaping the Character of Environmental Care for Students in MTSN 3 Tulungagung in accordance with the plan was proven from the habituation of madrasah residents.